Cladocerans of Alona affinis group (Cladocera: Anomopoda: Chydoridae) from North America - Sinev, Artem Y. (Zootaxa, 2013)
Cladocera of Alona affinis group from North America preserved in the collection of Professor D. G. Frey were investigated. A new subspecies of Alona ossiani Sinev, 1998 is described. Alona ossiani herricki ssp. nov. differs from the nominative subspecies in presence of 2–3 marginal denticles on postanal angle of male postabdomen, no differences between subspecies were revealed in the female morphology. An obscure taxon Alona lepida Birge,1892 was shown to be a valid species of affinis-group and is redescribed. A. lepida shares characteristic features of the group, but differs from all other species in the body shape, by postabdominal claw with basal spine almost parallel to the claw itself, and by IDL seta 1 being not claw-like. Morphology, relationships and distribution of studied taxa are discussed.